2016
DOI: 10.1016/j.jaap.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of n-pentane pyrolysis at elevated temperatures and pressures in a variable pressure flow reactor

Abstract: Thermally cracking fuel in a fuel processing facility or undergoing pyrolysis in the anode channel of a fuel cell can lead to coke deposition. The formation of coke occurs via chemical kinetic pathways that are largely dependent on poly aromatic hydrocarbons (PAHs). The formation of PAH's largely depends on species which include ethylene, acetylene, butadiene, benzene and toluene. Pentane is a relatively simple structure for modeling purposes, yet large enough that it produces some of the relevant chemistry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…It is important to reconcile the above conclusions with other reports which have found acid-catalyzed cracking reactions to be endothermic. One possibility is that the endothermic reactions in previous work were actually the result of homogeneous pyrolysis . Pyrolysis of alkanes can produce significant quantities of ethylene, which would be highly desirable for this application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to reconcile the above conclusions with other reports which have found acid-catalyzed cracking reactions to be endothermic. One possibility is that the endothermic reactions in previous work were actually the result of homogeneous pyrolysis . Pyrolysis of alkanes can produce significant quantities of ethylene, which would be highly desirable for this application.…”
Section: Discussionmentioning
confidence: 99%
“…The homogeneous reactions will only be important at higher temperatures, a primary reason we chose to work at temperatures below 800 K. In the work of Huang et al, homogeneous, endothermic reactions with n -octane as fuel became significant above ∼873 K, even at high fuel flow rates. In another example, Saldana and Bogin reported that 10% of n -pentane is converted in 0.6 s at 923 K …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the temperature for manufacturing carbonaceous materials ranges from 1000 to 4000 K, in the cases of arc discharge, CVD, laser ablation, pyrolysis, , and combustion. , The high temperature contributes to the atomic C formation from initial reactants. Thus, the nucleation and growth mechanisms of carbonaceous materials at high temperature can simply be seen as the self-assembly of atomic C. For this, many kinetic models have been developed to describe the pyrolysis of hydrocarbons. Nevertheless, these models were employed to compare and fit the elementary reactions with experimental observations to determine dominant reactions in the total conversions alone and cannot provide any dynamic detail at the atomic level. Using reactive molecular dynamics (RMD), our recent work indicated that the pyrolysis product of CH 4 is an orderly cavity-like carbonaceous material as a possible precursor of CNTs, while that of acetylene (C 2 H 2 ) is a disorderly C black .…”
Section: Introductionmentioning
confidence: 99%